Interactions between working memory and creativity: A systematic review - Remoli, Taís Crema [UNESP]; Santos, Flávia Heloísa [UNESP] (Universidade Estadual de Maringa, 2017)
Creativity and working memory are academic and professional success markers. Paradoxically, correlational studies do not always find associations between these constructs; some studies show positive associations between them and others show negative associations. Probably, the contradictory findings arise from different parameters, because of that it is important to identify them in order to have a more coherent understanding of this relationship. Thus, this systematic literature review aimed to answer the questions: What is the relationship between working memory and creativity? Do update and serial recall mnemonic processes also interfere in the production of convergent or divergent thinking? For this purpose, a survey of specific descriptors generated 384 articles found in Scopus, Web of Science and Pubmed databases, from which fifteen studies were selected. Despite the methodological variability between the selected studies, the results found suggest association between working memory and creativity, which are explained by the attentional, inhibitory, analytical and motivational processes involved. A systematic review of these studies concluded that the characteristics of experimental tasks to study creativity and working memory used can influence the results of this association. It is also possible to infer that working memory overload can impair creative performance.
Keywords: Creativity; Divergent thinking; Working memory